Modeled Effects of Traffic Fleet Composition on the Toxicity of Volatile Organic Compound Emissions. Issue 1 (2016) - Caviedes, Álvaro; Bigazzi, Alexander Y.; Figliozzi, Miguel
Motor vehicle emissions include many different compounds that have different levels of toxicity in humans. Volatile organic compounds (VOCs) are components of motor vehicle emissions with varying effects on human health and cancer risks. Proportional emission rates among compounds can vary substantially by vehicle and fuel type. This study addressed the question of how traffic fleet composition affects the toxicity of VOC emissions. Using inhalation unit risk estimates from the U.S. Environmental Protection Agency, VOC risk profiles were quantified for vehicle–fuel type combinations, light-duty and heavy-duty vehicle fleets, and roadway facility types (on-network and off-network). Of 14 modeled VOCs, formaldehyde, benzene, naphthalene, and 1, 3-butadiene contribute most to the cumulative risk of vehicle emissions. Formaldehyde and naphthalene are mainly emitted by diesel vehicles; benzene and 1, 3-butadiene are mainly emitted by gasoline vehicles. Cumulative VOC risk generated per on-network vehicle mile is four times higher for a gasoline heavy-duty vehicle and eight times higher for a diesel heavy-duty vehicle than for a gasoline light-duty vehicle. Off-network, cumulative VOC risk generated per vehicle is twice as high for gasoline heavy-duty vehicles as for diesel heavy-duty vehicles or gasoline light-duty vehicles. A case study of lane management strategies demonstrated how traffic management can change a VOC emissions risk profile and that changes in VOC emissions risk are different from changes in VOC emissions mass.